2012
DOI: 10.1111/all.12018
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to acid‐hydrolyzed wheat protein by transdermal administration to BALB/c mice, and comparison with gluten

Abstract: Transdermal exposure to HWP1 is sufficient to activate key immune pathways necessary for sensitizing mice for immediate hypersensitivity reactions. This study shows that HWP has a sensitizing potential as well as gluten, whereas its allergenicity may be different from that of gluten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…Different food allergens have been used in the animal models such as peanut, hazelnut, and cashew nut protein extracts, and hen’s egg ovalbumin (OVA), resulting in elevated levels of antigen-specific IgE [24-27]. Few animal studies have investigated allergic reactions towards hydrolysed wheat products [28-30]. In this study, the aim was to establish an animal model for food allergy skin sensitisation and investigate the sensitising capacity of an unmodified and an acid-hydrolysed gluten product in naïve versus tolerant Brown Norway (BN) rats.…”
Section: Introductionmentioning
confidence: 99%
“…Different food allergens have been used in the animal models such as peanut, hazelnut, and cashew nut protein extracts, and hen’s egg ovalbumin (OVA), resulting in elevated levels of antigen-specific IgE [24-27]. Few animal studies have investigated allergic reactions towards hydrolysed wheat products [28-30]. In this study, the aim was to establish an animal model for food allergy skin sensitisation and investigate the sensitising capacity of an unmodified and an acid-hydrolysed gluten product in naïve versus tolerant Brown Norway (BN) rats.…”
Section: Introductionmentioning
confidence: 99%
“…They studied IgE responses, intestinal permeability, intestinal anaphylaxis, and gut histamine release. Adachi et al [14] reported a transdermal sensitization model using acid-hydrolyzed gluten [14]. They studied IgE responses and anaphylaxis upon IP challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous models, our model differs significantly in a number of ways. Firstly, we used SSWP extract for the first time; previous models used the alcohol-soluble proteins or purified LTP [10,11,12,13,14]. Secondly, we quantified the HSRs; among the previous models, only Adachi et al [14] reported the utility of HSR for gluten sensitization [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations